Pengaruh Sekolah Secara Online terhadap Perilaku Sedentari yang Berisiko Obesitas pada Remaja Berumur 15-19 Tahun - Sinulingga, Pika Asyera; Andayani, Lita Sri; Lubis, Zulhaida (Jurnal Kesehatan, 2021)
Obesity is the accumulation of excessive fat in the body as a result of an imbalance in the amount of energy that enters and leaves the body. One of the causes of obesity is sedentary behavior. Sedentary behavior makes the activity passive. Behavior changes are also happening at this time due to the Covid-19 pandemic. Pandemic makes all activities to be carried out from the home to prevent the spread of the Covid-19 virus, like studying from home. Online school is considered more passive than offline school because when a rest period that can be used for physical movement through interacting with friends like playing together. Whereas online school, teenagers are only more dominant in being silent in front of a laptop or smartphone. This study aims to determine the effect of online school on sedentary behavior at risk of obesity in adolescents. This type of research is a quantitative study using a cross-sectional design. The number of respondents in this study consisted of 267 people. Data was obtained through the results of questionnaires which were conducted online using Google Forms. The results showed that online schools had a high risk of sedentary behavior by 49,1%, 44.9% of moderate risk, and less risk by 6,0%. Statistical test using chi-square obtained p-value=0,008 (<Î±=0,05). So it can be concluded that there is an effect of online schooling on sedentary behavior that is at risk of obesity in adolescents aged 15-19 years in the city of Medan.